PEMBUATAN TAS BERNILAI ESTETIS DARI KULIT KERANG UNTUK MENINGKATKAN PENDAPATAN KELOMPOK PEREMPUAN NELAYAN - Surni, Surni; Azis Muthalib, Dzulfikri (Jurnal Pengabdian Masyarakat Berkarya, 2025)
Making Aesthetically Valuable Bags from Seashells to Increase the Income of Fisherwomen's Groups. This community service programme aims to empower a group of fisherwomen by making aesthetically pleasing bags from seashell waste. This initiative utilises the abundant potential of marine waste in coastal areas to create eco-friendly fashion products with high economic value. Implementation methods included training in material processing techniques, product design, and digital marketing over 6 months. The results showed a significant improvement in participants' skills, with 90% of group members able to produce bags independently. From an economic aspect, there was an average income increase of 200% (from Rp750,000 to Rp2,250,000 per month). The programme not only improved community welfare but also contributed to a 40% reduction in beach waste. These findings prove that a local resource-based empowerment approach can be a sustainable solution for coastal communities.